CLIMATE INDICATORS FOR A WATERSHED IN THE EASTERN AMAZON - Tavares, Alexandra Lima; Carmo, Alexandre Mello Casseb do; Silva Júnior, Renato Oliveira da; Souza-Filho, Pedro Walfir Martins e; Silva, Márcio Souza da; Ferreira, Douglas Batista da Silva; Nascimento Júnior, Wilson da Rocha; Dall'agnol, Roberto (Revista Brasileira de Climatologia, 2021)
The present study compares the climatological normals for periods of 36 and 34 years (interpolated data) and observed precipitation and air temperature data (2015 and 2016) for four weather stations located within the boundaries of the Itacaiúnas River Watershed (IRW), with the historical data from the Marabá station in the eastern Amazon used as control data. Both the interpolated and observed data were validated with the control data. The quantile technique was used to identify annual precipitation intensity thresholds and seasonal periods. A comparison was made with the precipitation and air temperature data to determine the effects of ENSO events during the period from 1980 to 2016. Our results regarding annual variability showed that the Onça Puma station was the rainiest among the subareas studied. The month of March was characterized as the rainiest month, and July was the least rainy for the watershed area. The influence of ENSO events on air temperature occurred in the early years, from 1980 to 2003, and the stronger events had a greater influence on precipitation in the IRW area. The 2015/16 El Niño may have had a more pronounced effect on the rainfall behavior at the Fazenda Abadia and Sossego stations. In the Salobo station (forest area), there was a delay in precipitation curves related to the occurrence of ENSO events, which may be associated with temporal variations in the dynamics of soil-vegetation-atmosphere interactions.